THE USE OF COMPETITIVE COMMERCIAL INTELLIGENCE IN FAVOR OF BUSINESS GROWTH AND STRATEGIC DECISION MAKING - Polisel, Ulisses; Del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
The market is increasingly fierce, the result of new brands, products, services and technologies constantly launched or inaugurated. Being able to anticipate your challenges, identify opportunities and have offers that are more in line with consumer demand is not a differentiator, but a necessity for companies to survive and progress. Put in this way, this study seeks to evaluate the concept of Competitive Business Intelligence and what are its advantages in terms of integrating departments, sharing information, connecting to the public, or even offering a solid data base for making managerial decisions. To verify the pertinence of the concept, the study presents interviews with experienced managers of companies from different segments, in order to analyze how they use, in practice, Competitive Business Intelligence. What can be seen from this study is that the more companies use intelligent management concepts, the more they can benefit both in terms of market growth and in the alignment of products and services that are better designed to the demands of potential consumers.